Making it Matter: Reframing the U.S. Survey - Jesse Kohn (Radical Teacher, 2016)
In thinking about how we can teach Black Lives Matter in a U.S. survey, this essay suggests beginning the course with two readings: Ta-Nehisi Coates' "The Case for Reparations" and Amiri Baraka's Dutchman.  These texts can be used to place Black Lives Matters in historical context, question normative narratives of American history, and encourage student activism in their schools and communities.